STRATEGI PEMBELAJARAN BAHASA ARAB DI INSUTUT AGAMA ISLAM NEGERI PALU - Ahmad Asse; Nursyam Nursyam (ISTIQRA, 2014)
This study in respect of Arabic strategies in IAIN Palu aimed at to know the strategies used by the lecturer of Arabic learning in IAIN. This study is a qualitative research, data collection is done by using observation, interview, and documentation. Data analysis was performed by giving meaning to the data collected, and of the meaning that is drawn a conclusion. The results showed: 1). The influence happy and whether students in learning Arabic one of which depends on the strategies used by lecturers in teaching, while the Arabic language learning strategies used by lecturers at IAIN Palu can vary and the researchers wrote that: Strategies Istima 'qirÄ'ah strategy: this strategy is used by lecturers so that students want to listen to what is read by faculty and students watched, Kalam strategy, strategy and strategy kitabah Qawaid. (2) the constraints and solutions in the Arabic language learning strategies were the strategy when using that there are students who are eager to learn Arabic, there are also students who do not care about learning Arabic because he felt that Arabic is a difficult language, but the faculty continue to strive so that the students happy with the Arabic language lessons by giving motivation of students. And most of the students are not the spirit of the Arabic language lessons is a graduate student in addition to the MAN and boarding school